Physicochemical characterization of the formation of chitosan/xanthan gum-based polyelectrolyte complexes as ibuprofen carriers - Ćirić, Ana; Djekić, Ljiljana (Archives of Pharmacy, 2022)
By mixing the dispersions of oppositely charged polymers, intermolecular interactions are established and polyelectrolyte complexes (PECs) are formed. These interactions can differ in strength and extent, which can be influenced by the presence of the drug in the complex. The aim of this study was the physicochemical characterization of the formation of chitosan (CH)/xanthan gum (XG)-based placebo and ibuprofen-loaded PEC. The course of the PECs formation process was monitored by measuring the transmittance, which was reduced by adding XG dispersion, without or with ibuprofen, into CH dispersion whose initial transmittance was 97.53±0.64%. The final transmittance was 11.51±2.98% for placebo and 0.29±0.10% for ibuprofen-loaded PEC. The decrease in transmittance indicated the formation of complexes by establishing interactions between polymers and ibuprofen. CH dispersion had a Newtonian type of flow, while XG dispersions without and with ibuprofen and PEC hydrogels had pseudoplastic flow with thixotropy. The maximum apparent viscosities (ηmax at 22.2 s-1) of PEC hydrogels (1.65±0.06 Pa·s for placebo and 2.18±0.04 Pa·s for ibuprofen-loaded PEC) were higher compared to the dynamic viscosity of CH dispersion (0.09±0.01 Pa·s) and ηmax of XG dispersion without (0.20±0.00 Pa·s) and with ibuprofen (0.22±0.00 Pa·s). The measured increase of maximum apparent viscosities in PEC hydrogels confirmed the formation of complexes. Higher apparent viscosities corresponded to stronger interactions within PECs. Interactions were stronger in ibuprofen-loaded compared to placebo PEC, so it can be assumed that the ibuprofen entrapment can result in its controlled release from the carrier.